Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

A T-DINEOF model for multiple oceanic variables reconstruction - Bo Ping; Ruiting Yang; Yunshan Meng; Fenzhen Su; Cunjin Xue (Ocean Science, 2026)
Satellite-derived oceanic data are frequently affected by cloud cover, resulting in spatiotemporal gaps. The Multi-DINEOF method is widely used to reconstruct multiple oceanic variables. However, Multi-DINEOF essentially remains a matrix-based DINEOF approach and does not fully leverage the correlations among multiple variables. To address this limitation, this study proposes the T-DINEOF model, aiming to improve the accuracy of reconstructing multiple oceanic variables simultaneously. When applied to sea surface temperature (SST), sea surface chlorophyll a (SCHL), and sea surface wind (SSW) collectively, T-DINEOF reduces root mean square error (RMSE) by 12.9 %, mean absolute error (MAE) by 13.8 %, and mean absolute percentage error (MAPE) by 11.9 % compared to Multi-DINEOF. For each individual oceanic variable, T-DINEOF outperforms both Multi-DINEOF and the original DINEOF methods, reducing RMSE by 9.0 % and 14.7 %, MAE by 10.5 % and 14.6 %, and MAPE by 13.7 % and 13.4 % for SST; reducing RMSE by 9.3 % and 11.8 %, MAE by 9.9 % and 13.4 %, and MAPE by 8.3 % and 11.8 % for SCHL; and reducing RMSE by 16.6 % and 3.7 %, MAE by 16.8 % and 3.5 %, and MAPE by 16.4 % and 3.1 % for SSW. Additionally, T-DINEOF proves effective in regions with a high proportion of missing data and in cases of low data correlation.

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Repurposing hydrothermal carbonization aqueous product: Leveraging nitrification inhibition to drive a stable assimilatory metabolism for nutrient recovery - Ruiting Zhang; Hong Chen; Jun Sheng; Shiyi Zhao; Xin Yu; Dong Cheng; Hanyue Wu; Xiaoming Zou; Gang Xue (Chemical Engineering Journal, 2026)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Experimental evaluation of the impact of CO2/N2 mixture on residual water saturation during CO2 storage in saline aquifer - Yi Li; Wendong Dan; Jiaqi Zhao; Zhikai Hu; Ruiting Suo; Liang Xue; Li He; Qingchun Yu (Journal of Contaminant Hydrology, 2025)

Sulfur cycle, a new opportunity for nitrogen removal from textile wastewater: A review - Shiyi Zhao; Hong Chen; Jun Sheng; Xin Yu; Kejia Zeng; Dong Cheng; Hanyue Wu; Ruiting Zhang; Xianbao Xu; Xiaoming Zou; Gang Xue (Journal of Water Process Engineering, 2024)

Gut microbiota modulation by L-Fucose as a strategy to alleviate Ochratoxin A toxicity on primordial follicle formation - Ruiting Wang; Jie Song; Muyu Cai; Yuan Xue; Jing Liu; Ning Zuo; Massimo De Felici; Junjie Wang; Wei Shen; Xiaofeng Sun (Journal of Hazardous Materials, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)